Situating 1816, the ‘year without summer’, in the UK - Veale, Lucy; Endfield, Georgina H. (Wiley, 2016)
The immediate local impacts of the eruption of Mount Tambora, Sumbawa, Indonesia in April 1815 were devastating, resulting in the loss of an estimated 60 000 lives on this and neighbouring islands. However, the longer term effects of the largest known historical eruption on global weather and climate and the related consequences for human health and wellbeing have maintained the prominence of the eruption in public memory. Among the most notable effects were global weather anomalies the following year, which has come to be referred to as ‘the year without summer’. Scholars across the sciences and humanities continue to investigate the eruption, seeking insights into the likely meteorological and societal impacts of future volcanic eruptions. The bicentenary of the ‘year without summer’ in 2016 provides a timely moment to revisit this weather episode. In this paper, we draw on a range of archival materials and contemporary publications to reconstruct the weather year and explore how the summer of 1816 was experienced and recorded across the UK. We also wish to demonstrate the importance of historical contingency in understanding the potential implications of the event at the local level, and of situating events within their appropriate temporal context. We do this by considering the summer of 1816 as set against the wider weather and cultural contexts of the 1810s. Our findings illustrate that in a UK context, summer 1816 was characterised by unusual and extreme weather events. Importantly it also took place within a sequence of years that were similarly replete with anomalous and challenging weather conditions.